Arte popular peruano : colección de piezas de artesanía donada a Cuba por Alicia Bustamante (Galeria Latinoamericana, 1972)
Grid with photographs of samples of Peruvian art and of artists at work Poster advertising exhibition of Peruvian arts and crafts, held in Havana, February, 1972 PO-1406